STRENGTHENING DIGITAL-BASED CIVICS EDUCATION IN PREVENTING CYBERBULLYING AMONG VOCATIONAL HIGH SCHOOL STUDENTS AT SMK PRAMA ARTHA SERBELAWAN - Ukur, Jumpa; Suhendar, Aris; Sirait, Iuska Roito; Ababbil, Tamara Nur; Anshari, Nayla Nur (Program Pascasarjana UIN Sumatera Utara, 2025)
The increasing prevalence of cyberbullying among vocational high school students poses a serious challenge in the field of education. This study aims to analyze strategies for strengthening digital-based Civics Education (PPKn) as an effort to prevent cyberbullying. Using a descriptive qualitative approach with a case study method, data were collected through participatory observation, in-depth interviews, and document analysis at SMK Prama Artha Serbelawan. The results show that the integration of problem-based learning and experiential learning models in PPKn effectively enhances students' digital literacy, media ethics, and awareness of digital responsibility. The study concludes that digital-based Civics Education plays a significant role in shaping students’ character as active and responsible digital citizens.